Crystallization of polymers from stressed melts - Kumaraswamy, Guruswamy (Journal of Macromolecular Science-Polymer Reviews, 2005)
In the last decade, there have been several investigations into the route by which a polymer melt that has been subjected to flow transforms into a crystalline state. Crystallization of polymers from flowing or stressed melts is a technologically important problem since most thermoplastics are subjected to intense flow fields during normal processing operations. The renewed interest in this problem is due to the availability of new experimental tools that, coupled with advances in modeling and simulations, are beginning to yield insights into the molecular characteristics that control the crystallization pathways adopted by a stressed polymer melt. Recent evidence conclusively implicates the high molecular weight tail in promoting crystallization on shearing. It appears that the formation of oriented nuclei in polydisperse melts is controlled by chain orientation of a small fraction of high molecular weight chains in a melt. Thus, it is the theological criteria for ``critical'' chain orientation that govern flow-induced acceleration and orientation in polymer crystallization. This review summarizes the literature on the effect of shearing on polymer crystallization, and focuses on recent advances in understanding the role of molecular parameters that couple polymer crystallization to flow and melt orientation.
Keywords: flow; polymer crystallization; processing; shear